Adolescent track and field injuries presenting to US emergency departments - Hopkins, C.; Graham, B.; Donnelly, B.; Robertson, A.; Strange, J. (The Physician and Sportsmedicine, 2024)
Objectives Track and field (T&F) is a highly popular sport for adolescents. The diversity of running, jumping, and throwing events within the sport can result in unique injury patterns for adolescent track and field participants. The purpose of this study was to estimate injury risk in adolescent T&F and describe the types of injuries resulting in ED visits, classified by T&F events.